ANALISIS KESALAHAN MENYELESAIKAN SOAL TRANSAKSI JURNAL KHUSUS BERDASARKAN PROSEDUR NEWMAN’S ERROR ANALYSIS - Sisilia Venny; Herkulana Herkulana; M. Basri (Universitas Tanjungpura, 2021)
AbstractThis research aims to describe the errors in solving special journal transaction questions based on Newman’s Error Analysis Procedure for class X AKL at SMK Kristen Immanuel II Sungai Raya. The research method used in this qualitative method with data procedures using tests and interviews. The results showed that, 1) there has been a Reading Error (R), The errors experienced are not correct in writing important words and are incomplete. 2) There has been comprehension Error (C), inaccurate and incorrect, and incorrect errors in the account name records. The form of understanding is not written in the form of accounting analysis. 3) there has been a Transformation Error (T), an error that is not enough to use the formula in accounting. 4) there has been a process skill Error (P), an error experienced by a transformation error. 5) There has been Encoding Error (E), errors experienced are inaccurate and errors are influenced by transformation errors.Keywords: Error Analysis, Newman Error Analysis, Special Journal, Transaction Question